Shrinkage Behaviors of Conventional Sintered Dental Zirconia - Nidal W. Elshereksi; Mohamed M. Aboras (African Journal of Advanced Pure and Applied Sciences, 2024)
Shrinkage is a critical phenomenon throughout the sintering of dental ceramics as it disturbs the structural and physical behaviors. In the present paper, the shrinkage behavior of pre-sintered and sintered zirconia blocks were investigated. The physical attributes such as density and porosity were also evaluated. Three experimental groups of dental zirconia blocks were designed and fabricated from commercial dental zirconia blocks (HT4, 89HT and A214). A total of 12 discs of zirconia samples were then prepared. The density and porosity of pre-sintered and sintered zirconia samples from various brands were computed. The linear and volumetric shrinkages of zirconia samples were computed and evaluated. The outcomes exhibited that the sintering temperature led to the densification of zirconia samples and the relative density values reached up to 97.5%, 94.8% and 93% for HT4, 89HT and A214 respectively. As the density of zirconia samples increased, a dramatic decrease in the pores content after the sintering process was observed. The densification process was accompanied by a degree of contraction. When the linear shrinkage of HT4, 98HT and A214 were 20.27%, 20.74% and 19.58% respectively, they achieved 49.37%, 48.5% and 48.27% as volumetric shrinkage. The shrinking value of all tested zirconia met the clinical application requirements.